Improvement of photocatalytic activity of silver nanoparticles by radio frequency oxygen plasma irradiation. (2nd July 2015) - Fang, Yingcui; Zhang, Bing; Hong, Liu; Yao, Damao; Xie, Zhiqiang; Jiang, Yang
Abstract: Photocatalytic activity (PA) of silver nanoparticles (AgNPs) induced by radio frequency (RF) oxygen plasma irradiation (OPI) is investigated in this paper. An improvement in PA by 365% and 181% has been achieved when 15 nm AgNPs irradiated by oxygen plasma for 2 s were used to degrade 10 −5 M Rhodamine 6 G (R6G) under ultraviolet (UV) and visible lights, respectively. The PA caused by OPI is better than that induced by the localized surface plasma resonance (LSPR) of AgNPs. The mechanism for the improvement was explored by scanning electron microscopy (SEM), x-ray photoelectron spectroscopy (XPS) and UV–vis absorption spectra. The OPI-induced formation of AgO/AgNP and Ag2 O/AgNP-heterogeneous photocatalysts and electrophilic oxygen are considered to be responsible for the PA improvement. This investigation deepens our understanding of oxygen-assisted photocatalysis of AgNPs and provides a practical approach using solar light for broad spectra photocatalysis with high efficiency.